Record low ozone values over the Arctic in boreal spring 2020 - Dameris, Martin; Loyola, Diego; Nützel, Matthias; Coldewey-Egbers, Melanie; Lerot, Christophe; Romahn, Fabian; Van Roozendael, Michel (Atmospheric Chemistry and Physics, 2021)
. Ozone data derived from the Tropospheric Monitoring Instrument (TROPOMI) sensor on board the Sentinel- 5 Precursor satellite show exceptionally low total ozone columns in the polar region of the Northern Hemisphere (Arctic) in spring 2020. Minimum total ozone column values around or below 220 Dobson units (DU) were seen over the Arctic for 5 weeks in March and early April 2020. Usually the persistence of such low total ozone column values in spring is only observed in the polar Southern Hemisphere (Antarctic) and not over the Arctic.